The epidemiology and management of ameloblastomas: A European multicenter study. Issue 12 (December 2021) - Boffano, Paolo; Cavarra, Francesco; Tricarico, Gerardo; Masu, Lavinia; Brucoli, Matteo; Ruslin, Muhammad; Forouzanfar, Tymour; Ridwan-Pramana, Angela; Rodríguez-Santamarta, Tanía; Rui Ranz, Marta; de Vicente, Juan Carlos; Starch- Jensen, Thomas; et al.
Abstract: The present study aimed at assessing the epidemiology including demographic variables, diagnostic features, and management of ameloblastomas at several European departments of maxillofacial and oral surgery. The following data were recorded for each patient: gender, age, voluptuary habits, comorbidities, site, size, radiographic features, type, histopathological features, kind of treatment, length of hospital stay, complications, recurrence, management and complications of the recurrence. A total of 244 patients, 134 males and 110 females with ameloblastomas were included in the study. Mean age was 47.4 years. In all, 81% of lesions were found in the mandible, whereas 19% were found in the maxilla. Mean size of included ameloblastomas was 38.9 mm. The most frequently performed treatment option was enucleation plus curettage/peripheral ostectomy in 94 ameloblastomas, followed by segmental resection (60 patients), simple enucleation (46 patients), and marginal resection (40 patients). A recurrence (with a mean follow up of 5 years) was observed in 47 cases out of 244 ameloblastomas (19.3%). Segmental resection was associated with a low risk of recurrence (p = 0003), whereas enucleation plus curettage/peripheral ostectomy was associated with a high risk of recurrence (p = 0002). A multilocular radiographic appearance was associated with a high risk of recurrence (p < .05), as well as the benign solid/multicystic histologic type (p < .05). Within the limitations of the study it seems that the management of ameloblastomas will probably remain controversial even in the future. Balancing low surgical morbidity with a low recurrence rate is a difficult aim to reach.